Detection of Carbapenems and Colistin Resistance Genes in Pseudomonas aeruginosa and Acinetobacter baumannii: A Single-center Study in Iran - Tehrani, Shabnam; Samami, Hamed; Keyvanfar, Amirreza; Hashemi, Ali (Novelty in Biomedicine, 2022)
Background: This study aimed to determine carbapenems, colistin resistance genes, and antimicrobial susceptibility profiles of Pseudomonas aeruginosa and Acinetobacter baumannii isolates. Materials and Methods: In this cross-sectional study, specimens of patients with bloodstream, urinary tract, and surgical site nosocomial infections were enrolled. P. aeruginosa and A. baumannii isolates were identified using conventional methods. Antimicrobial susceptibility testing (AST) on isolates was performed using the disk diffusion method and minimum inhibitory concentration (MIC) for colistin as recommended by the Clinical and Laboratory Standards Institute (CLSI). The combination meropenem disk method was used to detect metallo-β-lactamases (MBLs). The blaNDM, blaVIM, blaIMP, and mcr-1 genes were identified using the polymerase chain reaction (PCR) method and Sequencing. Results: Forty strains of P. aeruginosa and forty strains of A. baumannii were isolated from hospitalized patients. The overall prevalence of multidrug-resistance (MDR) was 50% and 95% in P. aeruginosa and A. baumannii isolates, respectively. Almost all the MDR isolates were resistant to cefepime and piperacillin. Colistin had significant inhibitory activity against the isolates. MBL was detected in 25.0% and 15.0% of clinical isolates of P. aeruginosa and A. baumannii, respectively. We detected no blaNDM, blaVIM, blaIMP, and mcr-1 genes in our A. baumannii isolates. Moreover, only three P. aeruginosa isolates were positive for blaIMP gene. Conclusion: The alarming proportion of MDR P. aeruginosa and A. baumannii isolates was reported in the current study. Effective infection prevention practices are required and AST should guide patients' treatment.